Comment on Wang et al.'s anonymous multi-receiver ID-based encryption scheme and its improved schemes. (1st January 2013) - Zhang, Jianhong; Xu, Yuwei; Zou, Jiancheng
As an important cryptographic primitive, anonymous receiver encryption can protect the privacy of the receiver. To achieve it, Fan et al. proposed an anonymous multi-receiver ID-based encryption by using Lagrange interpolating polynomial in 2010. However, Wang et al. showed that Fan et al.'s scheme did not satisfy the anonymity of the receivers. Then they provided an improved scheme to fix it and showed that the improved scheme was secure. Unfortunately, in this paper, we pointed out that Wang et al.'s improved scheme did not satisfy the receiver's anonymity by analysing the security of the scheme. After analysing the reason to produce such flaws, we gave two improved methods to achieve the anonymity of the receivers. In the first improved scheme, the ciphertext length and computation complexity of producing and recovering ciphertext are more efficient than the ones in Wang et al.'s scheme. Furthermore, the second improved scheme has less computation cost than the first improved scheme in terms of encryption and decryption. The cipher length is 512 + | E | + w bits. To the best of our knowledge, our second improved scheme is most efficient in terms of computational cost.